Engineering a dual vaccine against COVID-19 and tuberculosis - Guthrie, Carlyn Monèt; Tan, Xuejuan; Meeker, Amber Cherry; Self, Ashton Elisabeth; Liu, Lin; Cheng, Yong (Frontiers in Cellular and Infection Microbiology, 2023)
The COVID-19 pandemic, caused by SARS-CoV-2 virus, has been one of the top public health threats across the world over past three years. Mycobacterium bovis BCG is currently only licensed vaccine for tuberculosis, one of the deadliest infectious diseases in the world, that is caused by Mycobacterium tuberculosis. In the past decades, recombinant M.bovis BCG has been studied as a novel vaccine vector for other infectious diseases in humans besides tuberculosis, such as viral infections. In the current study, we generated a recombinant M. bovis BCG strain AspikeRBD that expresses a fusion protein consisting of M. tb Ag85A protein and the receptorbinding domain (RBD) of the SARS-CoV-2 spike protein using synthetic biology technique. Our results show that the recombinant M. bovis BCG strain successfully expressed the fusion protein.Interestingly, the recombinant M. bovis BCG strain AspikeRBD significantly induced a SARS-CoV-2 spike-specific T cell activation and IgG production in mice when compared to parental M.bovis BCG strain, and was more potent than recombinant M.bovis BCG strain expressing SARS-CoV-2 spike RBD alone. As expected, the recombinant M. bovis BCG strain AspikeRBD activated an increased the number of M. tb Ag85A-specific IFNγ-releasing T cells and an enhanced IgG production in mice when compared to parental M.bovis BCG strain or the BCG strain expressing SARS-CoV-2 spike RBD alone. Taken together, our results indicate a potential application of the recombinant M. bovis BCG strain AspikeRBD as a novel dual vaccine against SARS-CoV-2 and M. tb in humans.